Evaporation of a water layer under local non-isothermal heating; Applied Thermal Engineering; Vol. 219, Pt. A - Misyura S. Ya. Sergey Yakovlevich; Egorov R. I. Roman Igorevich; Morozov V. S. Vladimir Sergeevich; Zaitsev A. S. Aleksandr Sergeevich (2023, 2023)
Title screen